Measurements of the Z partial decay width into c(c)over-bar and multiplicity of charm quarks per b decay - Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (2000)
The partial decay width Rc of the Z into cc̄ quark pair and the number of charm quarks nc per b decay are measured with the DELPHI detector at LEP 1. Particle identification provides clear D0, D+, D+s and Λ+c signatures. The charm hadron production rate is measured in each channel by a fit to the scaled energy, impact parameter information and the invariant mass spectrum. Two measurements of Rc are presented, from the D*+ production rate and from the overall charm counting, including strange charm baryon production, in cc̄ events. The multiplicity nc, which includes hidden cc̄ and strange charm baryon production, is inferred from the charm counting in bb̄ events. The final results are Rc = 0.1665 ± 0.0095 and nc-= 1.166 ± 0.086.